Non-typhoidal Salmonella contributes to gastrointestinal infections in Morogoro: Evidence from patients attending Morogoro regional referral hospital in Tanzania. - Anacleta Cuco; Ernatus Mkupasi; Alexanda Mzula; Robinson Mdegela (Public Library of Science (PLoS), 2024)
Introduction Salmonella is one of the most common causes of food-borne outbreaks and infection worldwide. Non-typhoidal Salmonella (NTS) infections are common and remain a significant public health problem among important bacterial foodborne diseases. The current study aimed to establish the Non typhoidal Salmonella infection and antimicrobial resistance status among selected patients at Morogoro Regional Referral Hospital (MRRH), Morogoro Region, Tanzania, to inform clinical care management and public health interventions. Methodology A cross-sectional study was conducted using medical records and samples were collected from hospitalised and outpatients between October and December 2021. A total of 153 participants were enrolled in the study and 132 consented to being sampled. The collected samples were analysed using standard microbiological techniques. The isolates were subjected to molecular genotyping, where Polymerase Chain Reaction (PCR) was performed targeting the 16S rDNA gene. PCR products were then submitted for sequencing to establish phylogenetic relatedness. Antimicrobial susceptibility testing and resistance genes screening were also conducted. Results The phylogenetic analysis identified two Salmonella serovars; Salmonella Enteritidis and Salmonella Typhimurium. The isolates were from four adults and seven children patients. The isolates were tested against six antimicrobial agents: tetracycline, trimethoprim, gentamycin, ciprofloxacin, ampicillin and cefotaxime. Further antimicrobial assays were performed by screening 10 antimicrobial resistance genes using PCR. Overall, the highest resistance was observed in ampicillin (100%), whereas the lowest resistance was recorded for ciprofloxacin and gentamicin (9.1%). In addition, four (36.4%) of the isolates were resistant to cefotaxime and three (27.3%) to tetracycline and trimethoprim. The isolates also exhibit the presence of resistance genes for sulfamethoxazole 1&2, tetracycline (tet) A&B, Beta-lactamase CTXM, Beta-lactamase TEM, Beta-lactamase SHV, Gentamycine, Acra and acc3-1 in different occurrences. The overall prevalence of Salmonella species in Morogoro region was 8.3% (11/132) with Salmonella Enteritidis and Salmonella Typhimurium being the only serovars detected from adults and children stool samples. Conclusion Our investigation showed that both children and adults had been exposed to Salmonella spp. However, the occurrence of NTS was higher in children (5.3% (7/132) compared to adults (3.0% (4/132). To stop zoonotic infections and the development of antimicrobial resistance in the community, this calls for Infection Prevention and Control (IPC) and stewardship programmes on rational use of antimicrobials in both health facilities and at the community level.